PENGARUH SOCIAL MEDIA MARKETING DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PENGGUNAAN FINTECH CICIL.CO.ID MELALUI BRAND TRUST PADA MAHASISWA DI KOTA PEKANBARU - ,, Rendra Wasnury, Tania Aisya Nadila , Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine how much influence Social Media Marketing, Electronic Word of Mouth, and Brand Trust have on the Decision to Use of students in Pekanbaru City. Primary data was collected with a questionnaire as an instrument and structured interviews were used as a complement in proving the research results. This study used 96 students in Pekanbaru City who used Cicil fintech with the Non-Probability Sampling technique. The method used is Explanatory Research using Partial Least Square Structural Equation Modeling (PLS-SEM) and path analysis as a data testing flow and assisted by the SmartPLS application in terms of data processing. The results of this study indicate that: (1) Social Media Marketing has a negative and not significant effect on the Decision to Use (2) Electronic Word of Mouth has a positive and significant effect on the Decision to Use (3) Brand Trust has a positive and significant effect on the Decision to Use (4) Electronic Word of Mouth has a negative and not significant effect on Brand Trust (5) Social Media Marketing has a positive and significant effect on Brand Trust (6) Social Media Marketing has a positive and significant effect on Decisions to Use through Brand Trust (7) Electronic Word of Mouth has a negative effect and not significant to the decision to use through Brand Trust. Keywords: Social Media Marketing, Electronic Word of Mouth, Brand Trust, Decision To Use, Fintech.